High speed two-photon laser scanning stereomicroscopy for three-dimension tracking multiple particles simultaneously in three-dimension - Chen, Xun; Li, Yang; Chen, Peng; Yao, Hai; Ye, Tong (Frontiers in Photonics, 2022)
In this paper, we will describe a video rate two-photon laser scanning stereomicroscopy for imaging-based three-dimensional particle tracking. Using a resonant galvanometer, we have now achieved 30 volumes per second (frame size 512x512) in volumetric imaging. Owing to the pulse multiplexing and demultiplexing techniques, the system does not suffer the speed loss for taking two parallax views of a volume. The switching time between left and right views is reduced to several nanoseconds. The extremely fast view switching and high volumetric imaging speed allow us to track fast transport processes of nanoparticles in deep light-scattering media. For instance, in 1%-intralipid solution and fibrillar scaffolds, the tracking penetration depth can be around 400µm.